Skull anatomy and phylogenetic assessment of a large specimen of Ecteniniidae (Eucynodontia: Probainognathia) from the Upper Triassic of southern Brazil - Stefanello, Micheli; Müller, Rodrigo Temp; Kerber, Leonardo; Martínez, Ricardo N.; Dias-Da-Silva, Sérgio (Zootaxa, 2018)
Ecteniniidae comprises an endemic radiation of carnivore probainognathian cynodonts from the Late Triassic of South America. Three taxa have been included in this clade: Ecteninion lunensis Martínez et al., 1996 and Diegocanis elegans Martínez et al., 2013 from Argentina, and Trucidocynodon riograndensis Oliveira et al., 2010 from Brazil. Herein, a new specimen (skull and mandible) assigned to T. riograndensis from the Carnian of the Candelária Sequence (Southern Brazil) is described. A phylogenetic analysis recovered the new specimen as the sister taxon of the holotype of T. riograndensis, and both in a trichotomy with E. lunensis and D. elegans, all supporting the monophyly of Ecteniniidae. The new specimen of T. riograndensis is almost 20% larger than its holotype. Therefore, it represents one of the largest specimens of a carnivorous probainognathian from the Late Triassic known to date and contributes to knowledge of size variation in ecteniniids.